Media Power and the Rule of Law in the Rise of New Despotism: Lesson Learned from Indonesia, China, Russia, and Iran - Siti Raudhah Salma (Penerbit Goodwood, 2022)
Purpose: this study aims to seek an answer to these research questions: 1)